1934
DOI: 10.1084/jem.60.2.127
|View full text |Cite
|
Sign up to set email alerts
|

An Immunological Study of the a Substance or Acetyl Polysaccharide of Pneumococcus Type I

Abstract: 1. The A carbohydrate isolated from Type I pneumococcus by Pappenheimer and Enders, on the basis of elementary analysis, the presence of the acetyl group and its immunological properties, appears to be identical with the acetyl polysaccharide described by Avery and Goebel. 2. The A carbohydrate possesses a greater anti-opsonic action than either the deacetylated substance obtained by boiling in alkali or the soluble specific substance of Type I pneumococcus prepared according to the procedure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1935
1935
1956
1956

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Experiments by Dr. I. Ardelean, using the bactericidal technique employed in this laboratory (49), have also shown that in vitro these sera possess marked opsonizing properties versus young, fully encapsulated organisms. Unpublished experiments carried out several years ago by one of us (J. F. E.) had indicated that, in mice, 16 hours after establishment of an infection the therapeutic effect of Antipneumococcus Type I rabbit sera was superior to that of Antipneumococcus Type I horse sera which by various tests (agglutination, precipitation, effect in the bactericidal system, and mouse protective power) were of the very large numbers of cocci which may be present in the cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 76%
“…Experiments by Dr. I. Ardelean, using the bactericidal technique employed in this laboratory (49), have also shown that in vitro these sera possess marked opsonizing properties versus young, fully encapsulated organisms. Unpublished experiments carried out several years ago by one of us (J. F. E.) had indicated that, in mice, 16 hours after establishment of an infection the therapeutic effect of Antipneumococcus Type I rabbit sera was superior to that of Antipneumococcus Type I horse sera which by various tests (agglutination, precipitation, effect in the bactericidal system, and mouse protective power) were of the very large numbers of cocci which may be present in the cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 76%